Transnational organised crime in Malaysia - Ab Hamid, Zuraini; Mohamad Noor, Rafidah; Mohd Sheriff, Shukriah; Ab Aziz, Norjihan; Mohd Nor, Aishah; Kamaruzzaman, Suzanna; Jaarudin, Faizah (IIUM Press and Ministry of Home Affairs (IPSOM), 2025)
Transnational organised crime refers to any group that engages in ongoing criminal activities aimed at profit, disregarding national boundaries. According to the United Nations, major forms of transnational organised crime include drug trafficking, human trafficking, migrant smuggling, illicit arms trading, cybercrime, illegal wildlife trade, trafficking in natural resources and the distribution of counterfeit medicines. To combat these crimes, the United Nations Convention against Transnational Organized Crime (the Convention) was adopted through General Assembly resolution 55/25 on November 15, 2000. The Convention's primary objective, as stated in Article 1, is to enhance cooperation in preventing and addressing transnational organised crime more effectively. Organised crime is typically conducted by structured groups, defined in Article 2(a) of the Convention as groups of three or more individuals that collaborate over time to commit serious crimes for financial or material gain. The Convention focuses on serious crimes of a transnational nature involving organised criminal groups. Serious crime is characterised as any conduct punishable by a maximum imprisonment of at least four years or a more severe penalty. Regarding sanctions for transnational organised crime, the Convention allows individual States to determine their penalties, but Article 11(1) mandates that such penalties reflect the seriousness of the offence. Malaysia signed the Convention on September 26, 2002, recognising transnational organised crime as a significant global issue threatening national stability and security. Hence, to protect its security, Malaysia is committed to supporting measures to combat this crime at national and international levels. Recognising transnational organised crime is a global threat that impacts all nations, including Malaysia, the authors conducted research on the subject. This book brings together and presents a comprehensive collection of literature and open-source information on organised crime in Malaysia, structured into five chapters. These chapters address key areas such as drug trafficking, human trafficking and migrant smuggling, firearms trafficking, cybercrime, and wildlife trafficking. These topics were selected based on their relevance to Malaysia’s experiences and perspectives. Each chapter discusses definitions, crime backgrounds, governing legislation, and relevant legal cases in Malaysia. The aim of this book is to enhance our understanding of transnational organised crime from Malaysia's viewpoint. The book will shed light on challenges and strategies in combating organised crime, ultimately contributing to a more comprehensive and nuanced perspective on this critical issue.